Manfaat Pelaksanaan Uji Kompetensi Pramusaji Untuk Menjamin Kualitas Pelayanan Restoran di Kota Tomohon - Miriam Mahdalena Tukunang (PolimdoSains, 2020)
Abstract: The industry or restaurant business in Tomohon City has a very rapid growth. The purpose of this study was to analyze the benefits of competency assessment for waiters to ensure the quality of their services while working. The method used is a qualitative research method with a descriptive analysis model. The research was conducted at 10 restaurants in Tomohon City. The results showed that as a reflection or image of the restaurant, it was judged by the visiting guests, which was determined by the competence of the waiter who worked, including the expertise of the waiter in serving customers directly. This is very crucial in giving a good impression or image and giving satisfaction to customers because they feel comfortable. This of course cannot be separated from a competency or knowledge of the profession in providing a table during the service. The results also show the need for competent waiters to have qualifications that are truly recognized in their fields which can be developed through trainings whose credibility is tested and recognized by the Professional Certification Board. Professional certification aims to provide recognition of competencies that have been obtained through learning, training, as well as work experience.